NK cells produce high levels of IL‐10 early after allogeneic stem cell transplantation and suppress development of acute GVHD. Issue 2 (27th October 2017) - Chan, Yuen Ling Tracey; Zuo, Jianmin; Inman, Charlotte; Croft, Wayne; Begum, Jusnara; Croudace, Joanne; Kinsella, Francesca; Maggs, Luke; Nagra, Sandeep; Nunnick, Jane; Abbotts, Ben; Craddock, Charles; et al.
Abstract: Natural killer (NK) cells rapidly reconstitute following allogeneic stem cell transplantation (allo‐SCT), at the time when alloreactive T cell immunity is being established. We investigated very early NK cell reconstitution in 82 patients following T cell‐depleted allo‐SCT. NK cell number rapidly increased, exceeding T cell reconstitution such that the NK:T cell ratio was over 40 by day 14. NK cells at day 14 (NK‐14) were donor‐derived, intensely proliferating and expressed chemokine receptors targeted to lymphoid and peripheral tissue. Spontaneous production of the immunoregulatory cytokine IL‐10 was observed in over 70% of cells and transcription of cytokines and growth factors was augmented. NK‐14 cell number was inversely correlated with the incidence of grade II‐IV acute graft versus host disease (GVHD). These findings reveal that robust reconstitution of immunoregulatory NK cells by day 14 after allo‐SCT is an important determinant of the clinical outcome, suggesting that NK cells may suppress the development of the T cell‐mediated alloreactive immune response through production of IL‐10. Abstract : NK cells at day 14 following allo‐SCT are highly proliferating, express chemokine receptors targeted relevant tissue and spontaneous produce immunoregulatory cytokine IL‐10, which suggestes that these NK cells may suppress the development of the T cell‐mediated alloreactive immune response to prevent GvHD.